Growth of two crossbred buffalo calves subject to two suckling systems. Technical note - Gallego, Carlos; Gonz?lez, Mar?a E.; Sarduy, Luc?a (Cuban Journal of Agricultural Science, 2011)
Birth weight (BW), average daily weight gain (ADWG), live weight at two months of age (LW2m), and weaning weight (WW) adjusted at seven months were analyzed to study the weight gain of buffalo calves of the Buffalypso breed (Bubalus bubalis), from 10 d up to two months of age, through two suckling systems. Thirty-four buffalo calves were used and allotted into two groups, according to the suckling time after the milking: the restricted suckling (RS) group and that of middle suckling restriction (MSR), being kept for a period of two and six hours, respectively. After 60 d, and up to the weaning, the MSR group was managed in the same form as that of the RS. A one-way analysis of variance was conducted with fit of covariance for the BW. The general means of BW, LW2m and WW, for RS and MSR, were of 38.25?3.83 and 39.11?3.72, 53.63?3.87 and 71.33?3.64, 135.57?7.36 and 162.33?6.94 kg, respectively. No statistical differences were found as to the BW in both treatments, whereas there was significant statistical effect for the LW2m (P < 0.01) and WW (P < 0.05), favoring the MSR group, respectively. It is concluded that the animals that remain longer post-milking time in contact with their mother (MSR) showed better weight gain and, consequently, higher weaning weight throughout the study, compared with the group that remained shorter time with their mother (RS). Key words: suckling time, buffalo calves, weight gain.